Sandtray Therapy for Young Girls in A Shelter Home - Muhammad Razif Ismail; Salleh Amat; Ku Suhaila Ku Johari; Zuria Mahmu (Simposium Antar Bangsa Seminar dan Workshop)
Sandtray therapy involves the use of verbal, audio-visual and touch sensory that will make counselling sessions more comprehensive. Researches executed the interview and observation method in this qualitative study which involved four teenage girls at a shelter home. The data was obtained through verbal communication in group counselling using sandtray therapy and images of miniature arrangement in the sandtray, and was analysed using thematic process. The findings showed how sandtray therapy could help clients to visualize the issues more effectively and helped the counsellor to identify issues. Clients also showed positive emotional development and gained insights easier when they realized the negative emotions they held. Results of this study supported the use of sandtray therapy for girls in shelter homes.